1993
DOI: 10.1590/s0034-89101993000600006
|View full text |Cite
|
Sign up to set email alerts
|

Distribución de la caries dental en niños preescolares en una región urbana, Argentina, 1992

Abstract: YANKILEVICH, E.R.L.M. de et al. Distribución de la caries dental en niños preescolares en una región urbana, Argentina, 1992. Rev. Saúde Pública, 27: 436-44, 1993. Se describen los resultados de una investigación desarollada sobre una muestra de 1.115 preescolares (5 años) de jardines de infantes de la Ciudad de Córdoba (Argentina), destinada a establecer la prevalencia y distribución de la caries dental conforme a su nivel económicosocial. El estudio reveló que, respecto a 1973, la prevalencia de caries dismi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
6

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
(29 reference statements)
0
4
0
6
Order By: Relevance
“…Several studies have found a relationship between maternal education and oral health. 11,12,29 A m o n g c h i l d r e n w h o s e m o t h e r s h a d completed at most primary school, 77% had cavities or missing teeth, compared to 40% among those whose mothers had finished secondary school, and 13% among those whose mothers had completed tertiary school or university. These results evidence an urgent need to implement health equality consists of minimizing avoidable disparities together with their determinants among people with different levels of privilege or advantages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found a relationship between maternal education and oral health. 11,12,29 A m o n g c h i l d r e n w h o s e m o t h e r s h a d completed at most primary school, 77% had cavities or missing teeth, compared to 40% among those whose mothers had finished secondary school, and 13% among those whose mothers had completed tertiary school or university. These results evidence an urgent need to implement health equality consists of minimizing avoidable disparities together with their determinants among people with different levels of privilege or advantages.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] In different regions of Argentina, it was determined that children whose families had a lower income had a high level of oral diseases. 11,12 Child mortality rates vary depending on the population's socioeconomic status; being higher among groups with a high prevalence of unmet basic needs. 13,14 Epidemiological studies on child health indicators associated with living conditions allow to establish Original article the extent and distribution of inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a national study realized in Colombia in 2000 to assess the impact of the consumption of fluoridated salt showed 45.2% caries-free (18). In Cordova, Argentina, whose natural fluoride in the water has concentrations ranging from 0.8 to 1.0 ppm, 38% of the examined children were caries-free (19). In Europe, the percentage of children free of caries is lower.…”
Section: Caries Prevalencementioning
confidence: 93%
“…Mattila et al 44 encontraram maior possibilidade de filhos com ceo-d igual a zero quando as mães eram mais velhas, tinham maior escolaridade e ocupação profissional mais elevada. Diversas são as pesquisas que estabelecem uma forte associação entre experiência de cárie e indicadores socioeconômicos 39,[45][46][47][48][49][50][51] .…”
Section: Etiologia E Fatores De Risco Para O Desenvolvimento Da Doençunclassified